Stubborn roots : race, culture, and inequality in U.S. and South African schools - Carter, Prudence L. (New York ; Oxford : Oxford University Press, 2012)
The author shows how school communities can better incorporate previously disadvantaged groups and engender equity by addressing socio-cultural contexts and promoting 'cultural flexibility'. She also raises timely questions about the social, political, and philosophical purposes of multiracial schooling that have been greatly ignored by many, and cautions against narrow approaches to education that merely focus on test-scores and resources.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Apr. 26, 2012).
Keywords: Educational equalization -- United States -- Case studies; Educational equalization -- South Africa -- Case studies; Discrimination in education -- United States -- Case studies; Discrimination in education -- South Africa -- Case studies; Multiculturalism -- United States -- Case studies; Multiculturalism -- South Africa -- Case studies